The effect of fish hydrolysate addition to the standard feed and its storage duration to the total content of nitrogen in the excreta of laying chicken - Achmad Sjaifullah; Nanda Letitia Ivana; I Nyoman Adi Winata; Ika Oktavianawati (Faculty of Animal Science, Universitas Brawijaya, 2019)
The aim of this study is to determine the effect of the addition of fish hydrolyzate with variuos concentration to the standard feed and feed storage duration towards the decrease of odor by observing total nitrogen content in the excreta of laying chicken. 108 laying chicken aged forty-six weeks were divided into 12 (twelve) treatment combination. Each treatment consists of 9 (nine) laying chickens. All the laying chickens were kept in a battery cage and were fed with commercial standard feed which was added with fish hydrolysate in three different concentrations (0; 1; and 2%) during the 5-day feeding treatment period. Each standard feed which was added with different concentrations of fish hydrolysate were stored for a number of different day variations (0; 5; 10; and 15 days) before being fed to the laying chickens . The variables analyzed were water content and total nitrogen content in the excreta. Results showed that the total nitrogen content in the excreta was not affected (sig> 0.05) by the duration of feed storage but was significantly affected (sig <0.05) by the addition of fish hydrolyzate with different concentration. The use of fish hydrolyzate in 1-2% concentration reduce the levels of water content and total nitrogen content of laying chicken excreta.